2023
DOI: 10.1111/cge.14293
|View full text |Cite
|
Sign up to set email alerts
|

Novel variants in ACTL7A and PLCZ1 are associated with male infertility and total fertilization failure

Abstract: Total fertilization failure (TFF), which refers to fertilization failure in all mature oocytes, accounting for 5%-10% of in vitro fertilization (IVF) cycles and 1%-3% of intracytoplasmic sperm injection (ICSI) cycles in human. In this study, we recruited three unrelated primary infertile men with repeated cycles of TFF and performed whole-exome sequencing to identify the potential pathogenic variants. We identified homozygous or compound-heterozygous variants of paternal-effect genes ACTL7A and PLCZ1 that foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Those results are consistent with our study, couples with OAT can benefit from ICSI-AOA in terms of higher fertilization rate, which in turn increases the number of available embryos and may improve the implantation and pregnancy rates. Recent researches found novel sperm-related oocyte activators, which showed that the ACTL7A/PLCZ1 mutation and DPY19 deletion decreased the expression of functional PLCζ, resulting in acrosomal detachment and oocyte activation failure associated with male infertility, and ICSI-AOA could rescue TFF in individuals with the ACTL7A/PLCZ1/DPY19 pathogenic variants ( 9 , 25 , 26 ). However, ICSI-AOA is not always beneficial for patients with previous LFR and a suspected oocyte-related activation deficiency ( 27 ), except Vanden Meerschaut F et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those results are consistent with our study, couples with OAT can benefit from ICSI-AOA in terms of higher fertilization rate, which in turn increases the number of available embryos and may improve the implantation and pregnancy rates. Recent researches found novel sperm-related oocyte activators, which showed that the ACTL7A/PLCZ1 mutation and DPY19 deletion decreased the expression of functional PLCζ, resulting in acrosomal detachment and oocyte activation failure associated with male infertility, and ICSI-AOA could rescue TFF in individuals with the ACTL7A/PLCZ1/DPY19 pathogenic variants ( 9 , 25 , 26 ). However, ICSI-AOA is not always beneficial for patients with previous LFR and a suspected oocyte-related activation deficiency ( 27 ), except Vanden Meerschaut F et al.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal characteristics in the AOA group. decreased the expression of functional PLCz, resulting in acrosomal detachment and oocyte activation failure associated with male infertility, and ICSI-AOA could rescue TFF in individuals with the ACTL7A/PLCZ1/DPY19 pathogenic variants(9,25,26). However, ICSI-AOA is not always beneficial for patients with previous LFR and a suspected oocyte-related activation deficiency(27), except Vanden Meerschaut F et al reported that ICSI-AOA was very efficient in patients with a suspected oocyte-related activation deficiency and previous TFF after conventional ICSI.…”
mentioning
confidence: 99%